1970
DOI: 10.1002/pssb.19700420163
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of an amorphous antiferromagnet

Abstract: Recently, an effective field model of an amorphous antiferromagnet was discussed by Simpson (1). We have investigated the same system by a "computer experiment" (2) sol\iing the equation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The Cr3+ ions are coupled in an antiferromagnetic order, showing a negative-exchange interaction. Theoretical calculations as carried out by Simpson (1970), Kobe and Handrich (1970), and Hasegawa (1971) have shown that this is possible for the amorphous systems.…”
Section: Resultsmentioning
confidence: 98%
“…The Cr3+ ions are coupled in an antiferromagnetic order, showing a negative-exchange interaction. Theoretical calculations as carried out by Simpson (1970), Kobe and Handrich (1970), and Hasegawa (1971) have shown that this is possible for the amorphous systems.…”
Section: Resultsmentioning
confidence: 98%
“…F r o m equation (10) follows for t h e spin i in the ground state. F o r the crystalline case this expressior, reduces to that of F i s h e r (14), which is known to yield r a t h e r good r e s u l t s (15).…”
Section: K95mentioning
confidence: 99%
“…Theoretically the susceptibility was calculated within the molecular field approximation (9,10). Further in (11) it was shown that the well-known equality of the specific heat, free and internal energies, the absolute value of the (sublattice) magnetizations and the critical temperatures (T = T ) for the ferromagnet and C N the corresponding antiferromagnet (I.…”
mentioning
confidence: 99%